Tsunami Disaster Mitigation Education Based on Android Games at Hangtuah Belawan Senior High School - Rorisa, Monnavia; Susilawati; Fakhita Aulia Ghaida; Fiha Fauzia; Azhari Akmal Nasution (LPPM Universitas Mohammad Husni Thamrin, 2025)
Students attending schools in coastal areas are more vulnerable to the impacts of tsunamis, so knowledge and preparedness are very important to reduce disaster risks. Students can make better choices when a disaster occurs if they have adequate knowledge about early signs of a tsunami, evacuation procedures, and self-rescue techniques. This study examines the knowledge and preparedness levels of students at SMA Hang Tuah Belawan regarding tsunami disaster mitigation. The aim of this study is to evaluate the effectiveness of Android-based educational platforms and Kahoot in improving students' knowledge. Involving 54 students from grade X as respondents, this study uses a pre-test and post-test design. Teaching about tsunami mitigation is delivered through Android-based educational games, simulation videos, and interactive discussions. Meanwhile, pre-tests and post-tests use Kahoot as a data collection tool. The results of the study. Students attending schools in coastal areas are more vulnerable to the impacts of tsunamis, so knowledge and preparedness are very important to reduce disaster risks. Students can make better choices when a disaster occurs if they have adequate knowledge about early signs of a tsunami, evacuation procedures, and self-rescue techniques. This study examines the knowledge and preparedness levels of students at SMA Hang Tuah Belawan regarding tsunami disaster mitigation. The aim of this study is to evaluate how effective Android-based educational platforms and Kahoot are in improving students' knowledge. Involving 54 students from grade X as respondents, this study uses a pre-test and post-test design. Teaching about tsunami mitigation is delivered through Android-based educational games, simulation videos, and interactive discussions. Meanwhile, pre-tests and post-tests use Kahoot as a data collection tool.